2020
DOI: 10.1371/journal.pone.0238392
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of surgical management for recurrent intrahepatic cholangiocarcinoma: A multi-institutional study by the Okayama Study Group of HBP surgery

Abstract: Background The prognosis of intrahepatic cholangiocarcinoma (ICC) has been poor, because of the high recurrence rate even after curative surgery. This study aimed to evaluate the prognostic impact of surgical resection of recurrent ICC. Patients and methods A total of 345 cases of ICC who underwent hepatectomy with curative intent in 17 institutions were retrospectively analyzed, focusing on recurrence patterns and treatment modalities for recurrent ICC. Results Median survival time and overall 5-year recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
0
13
0
3
Order By: Relevance
“…Zhang et al (11) revealed that the patterns of early recurrence (≤2 years) and late recurrence were different, and early recurrence of extrahepatic recurrence was more common, whereas late recurrence was often only intrahepatic recurrence. Importantly, patients' recurrence within 1 year after surgery may represent more aggressive tumor biology, and a cutoff of 1 year after surgery has been used to distinguish the early recurrence and late recurrence in most studies (10,17,20,21). Wang et al (20) showed that specific risk factors, including CA 19-9, microvascular invasion, and multiple tumors, may relate to the early recurrence of ICC after curative resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (11) revealed that the patterns of early recurrence (≤2 years) and late recurrence were different, and early recurrence of extrahepatic recurrence was more common, whereas late recurrence was often only intrahepatic recurrence. Importantly, patients' recurrence within 1 year after surgery may represent more aggressive tumor biology, and a cutoff of 1 year after surgery has been used to distinguish the early recurrence and late recurrence in most studies (10,17,20,21). Wang et al (20) showed that specific risk factors, including CA 19-9, microvascular invasion, and multiple tumors, may relate to the early recurrence of ICC after curative resection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identifying patients who are at risk for early recurrence is important to construct individualized surveillance strategies for ICC patients after radical resection. Recently, more and more scholars are concerned about the risk factors of early recurrence, while the definition of early recurrence is different because definitive guidelines do not exist (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In a multi-center Japanese study, the re-resection rate was 31% for patients with intrahepatic-only recurrences occurring after a year from the initial operation. For patients with earlier recurrences, repeat surgery was performed in only 6.8% (132). Table 3 presents survival data after reresection of iCCA liver recurrences.…”
Section: Repeat Hepatectomymentioning
confidence: 99%
“…The main reason for the unfavorable outcome is the high incidence of recurrence [ 8 ]. Approximately 37.9–60% of patients occur local recurrence and/or distant metastases within 1 year after resection, with a median overall survival (OS) as low as 16.3 months [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%